2017
DOI: 10.3389/fevo.2017.00107
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Test of a Causal Link between Problem-Solving Performance and Reproductive Success in Wild Great Tits

Abstract: Recent studies have uncovered relationships between measures of various cognitive performances and proxies of fitness such as reproductive success in non-human animals. However, to better understand the evolution of cognition in the wild, we still have to determine the causality of these relationships and the underlying mechanisms. The cognitive ability of an individual may directly influence its ability to raise many and/or high quality young through for example its provisioning ability. Conversely, large and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…This may rely on a better processing and use of information sources about the environment (e.g., prioritize and memorize information but also learn from either personal or social experience), allowing individuals to optimally choose between alternatives (Mery, 2013). This is in line with previous results showing that higher problem-solving ability was associated with increased nestling provisioning rate (Cauchard et al, 2017), which could involve different habitat use strategies (e.g., range of territory use: Cole et al, 2012). Yet, empirical evidence that cognitive abilities influence the use of complex information for decision making in the wild is still extremely scarce.…”
Section: Linking Cognition and Fitness: The Role Of Information Procesupporting
confidence: 87%
See 2 more Smart Citations
“…This may rely on a better processing and use of information sources about the environment (e.g., prioritize and memorize information but also learn from either personal or social experience), allowing individuals to optimally choose between alternatives (Mery, 2013). This is in line with previous results showing that higher problem-solving ability was associated with increased nestling provisioning rate (Cauchard et al, 2017), which could involve different habitat use strategies (e.g., range of territory use: Cole et al, 2012). Yet, empirical evidence that cognitive abilities influence the use of complex information for decision making in the wild is still extremely scarce.…”
Section: Linking Cognition and Fitness: The Role Of Information Procesupporting
confidence: 87%
“…variance in learning performance, we found no relation between learning score and the probability to copy tit preference in males, whether yearling or older. These results suggest that cognitive abilities (in this study learning ability) can at least partly shape information use for decision-making, here in females, providing a new mechanistic explanation for the positive link between cognitive abilities and fitness components (Cauchard et al, 2017; see also Ducatez et al, 2020) that was previously observed in the wild (e.g., Keagy et al, 2011;Cauchard et al, 2013;Smith et al, 2015).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The relationship between innovative problem-solving and reproductive success, on the other hand, has been linked in some bird species to the ability to forage more efficiently (Cauchard et al, 2017;Preiszner et al, 2017;Wetzel, 2017) but see Cole et al (2012a). Access to food is a strong determinant of reproductive success among female hyenas; social rank is the strongest determinant of reproductive success because high ranking individuals enjoy the best access to high quality food resources (Holekamp et al, 1996).…”
Section: Mediators Of the Link Between Innovativeness And Fitnessmentioning
confidence: 99%
“…Similarly, Cole et al administered problem solving tests to great tits (Parus major), and successful problem solvers produced larger broods of chicks and were more efficient foragers for food (Cole et al, 2012; also see Ashton et al, 2018). Cauchard et al (2017) demonstrated that the link between cognitive abilities and brood size was causal in nature, i.e., while birds of higher cognitive abilities tended to maintain larger broods, direct manipulation of brood size did not in itself promote increases in cognitive ability. Other than reproductive behaviors, cognitive abilities sometimes predict other survival-related skills.…”
Section: Introductionmentioning
confidence: 99%